Penerapan Manajemen Strategi Menggunakan Metode SWOT dan QSPM pada Industri Kendang Jimbe UD. Karya Mandiri - Moch. Rizqi Abdillah; Yeni Roha Mahariani (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
This study aims to apply strategic management to the Jimbe Drum craftsman UMKM, UD. Karya Mandiri in Blitar City through Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis and Quantitative Strategic Planning Matrix (QSPM). The implementation of this strategic management is expected to help UMKM in formulating appropriate business development steps amidst the competition in the traditional musical instrument industry, while maximizing global market opportunities. The research method used is a quantitative descriptive approach with data collection techniques through observation, interviews, and distributing questionnaires to owners, employees, and consumers of UD. Karya Mandiri. The collected data were then analyzed using the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices to map the company's strengths, weaknesses, opportunities, and threats. The results of the analysis show that UD. Karya Mandiri's main strengths lie in high product quality, unique designs, and a good reputation in both local and national markets. A prominent weakness is the limited digital promotion, so that reach to the international market is not optimal. Opportunities that can be utilized are the increasing global market interest in traditional musical instruments, while threats include fluctuations in raw material prices, competition from similar products, and changes in music trends among young consumers. Based on the results of the IFE and EFE matrices, UD. Karya Mandiri's position is in quadrant I in the SWOT diagram, which indicates conditions for implementing aggressive strategies, such as market expansion and product diversification. The results of the QSPM analysis show that the priority strategy is export optimization by utilizing superior product quality, which obtained a Total Attractiveness Score (TAS) of 3.42. The implementation of this strategy is expected to expand market share, increase competitiveness at the global level, and strengthen the image of the Kendang Jimbe brand as a typical Indonesian product with high artistic value.